2011
DOI: 10.1007/s11664-011-1686-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of ENIG and ENEPIG as Surface Finishes for a Sn-Ag-Cu Solder Joint

Abstract: Interfacial reactions and joint reliability of Sn-3.0Ag-0.5Cu solder with two different surface finishes, electroless nickel-immersion gold (ENIG) and electroless nickel-electroless palladium-immersion gold (ENEPIG), were evaluated during a reflow process. We first compared the interfacial reactions of the two solder joints and also successfully revealed a connection between the interfacial reaction behavior and mechanical reliability. The Sn-Ag-Cu/ENIG joint exhibited a higher intermetallic compound (IMC) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(12 citation statements)
references
References 13 publications
4
7
0
1
Order By: Relevance
“…It can be clearly seen that the dominant intermetallic compound (IMC) formed was identified as (Cu,Ni)6Sn5 and exhibited rod-like and/or needle-shape morphology for the smaller and larger solder size. The present results are consistent with previous research [4]. The cross section view revealed that the IMC layer is formed at the SAC405/ EN(P)EPIG interface has a typical scallop-like morphology as represented in Fig 2. The thickness of this IMC layer for the Ø300µm solder was found to be 0.71µm which is relatively thinner than that recorded in the Ø700µm solder at 1.71µm.…”
Section: Methodssupporting
confidence: 93%
“…It can be clearly seen that the dominant intermetallic compound (IMC) formed was identified as (Cu,Ni)6Sn5 and exhibited rod-like and/or needle-shape morphology for the smaller and larger solder size. The present results are consistent with previous research [4]. The cross section view revealed that the IMC layer is formed at the SAC405/ EN(P)EPIG interface has a typical scallop-like morphology as represented in Fig 2. The thickness of this IMC layer for the Ø300µm solder was found to be 0.71µm which is relatively thinner than that recorded in the Ø700µm solder at 1.71µm.…”
Section: Methodssupporting
confidence: 93%
“…This is in good agreement with Tseng et al [12] and Azmah [6]. Moreover, the presence of the thin Pd layer in the ENEPIG finish may have suppressed the growth of the interfacial IMC layer and the consumption of the Ni(P) layer, resulting in the superior interfacial stability of the solder joint during prolonged reflowing at 260ºC [8]. The results seem to reconcile well with the above statement as the intermetallics formed on ENEPIG finish are more refined than those observed on ENIG finishes.…”
Section: Near Center Near Outsidesupporting
confidence: 90%
“…The ability of the IMC layer to catalyse βSn nucleation is expected to depend on factors including (i) the lattice match between the IMC and βSn, (ii) the wettability of the liquid and βSn on the IMC layer and (ii) the geometry of the IMC layer surface created by the layer roughness as discussed in [8,23]. At present, most soldering is performed using only a small range of substrates, surface finishes and/or under-bump metallizations (UBMs), mostly based on Cu, Ni, Ni-Pd or Ag [21,[24][25][26][27][28][29]. However, a much wider range of metallic elements could be used as solderable surfaces (in principle).…”
Section: Introductionmentioning
confidence: 99%